Effect of the microwave oven on structural, morphological and electrical properties of SrBi4Ti4O15 thin films grown on Pt/Ti/SiO2/Si substrates by a soft chemical method - Simões, Alexandre Zirpoli [UNESP]; Ramirez, M. A. [UNESP]; Riccardi, C. S. [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2008)
Thin films of SrBi4Ti4O15 (SBTi), a prototype of the Bi-layered-ferroelectric oxide family, were obtained by a soft chemical method and crystallized in a domestic microwave oven. For comparison, films were also crystallized in a conventional method at 700 degrees C for 2 h. Structural and morphological characterization of the SBTi thin films were investigated by Xray diffraction (XRD) and atomic force microscopy (AFM), respectively. Using platinum coated silicon substrates, the ferroelectric properties of the films were determined. Remanent polarization P-r and a coercive field E-c values of 5.1 mu C/cm(2) and 135 kV/cm for the film thermally treated in the microwave oven and 5.4 mu C/cm(2) and 85 kv/cm for the film thermally treated in conventional furnace were found. The films thermally treated in the conventional furnace exhibited excellent fatigue-free characteristics up to 10(10) switching cycles indicating that SBTi thin films are a promising material for use in non-volatile memories. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: thin films; atomic force microscopy; dielectric properties; fatigue